Missing Links: Digital Cinema, Analogical Archives, Film Historiography - Giuliani, Luca; Negri, Sabrina (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2011)
The sudden and permeating rise of digital technologies has been widely investigated by film critics and scholars. However, most studies tend to focus on the impact of digital technologies on contemporary film production, distribution, exhibition and the finished products it brings forth, reserving too little attention to the massive digitization of born-analog films. The production of digital motion pictures marks an unprecedented breaking point in history, putting the very nature of “film” and “cinema” at stake, while the digitization of film prints risks having an irreversible feedback effect on cinema's technological history. Focusing on two case studies—the 1995 restoration of the 1949 color version of Jacques Tati's Jour de fête and the discovery of some 16mm reels on nitrate stock in a collection deposited with the Museo Nazionale del Cinema in Torino, Italy—we illuminate the importance of technology for film historiography and reassert the need for a joint effort on the part of archives and academic institutions in the preservation of film memory for future generations.